Protocol for the evaluation of MRI artifacts caused by metal implants to assess the suitability of implants and the vulnerability of pulse sequences - Hilgenfeld, Tim; Prager, Marcel; Schwindling, Franz Sebastian; Jende, Johann; Rammelsberg, Peter; Bendszus, Martin; Heiland, Sabine; Jürchott, Alexander (JoVE. Video journal, 2018)
As the number of magnetic resonance imaging (MRI) scanners and patients with medical implants is constantly growing, radiologists increasingly encounter metallic implant-related artifacts in MRI, resulting in reduced image quality. Therefore, the MRI suitability of implants in terms of artifact volume, as well as the development of pulse sequences to reduce image artifacts, are becoming more and more important. Here, we present a comprehensive protocol which allows for a standardized evaluation of the artifact volume of implants on MRI. Furthermore, this protocol can be used to analyze the vulnerability of different pulse sequences to artifacts. The proposed protocol can be applied to T1- and T2-weighted images with or without fat-suppression and all passive implants. Furthermore, the procedure enables the separate and three-dimensional identification of signal loss and pile-up artifacts. As previous investigations differed greatly in evaluation methods, the comparability of their results was limited. Thus, standardized measurements of MRI artifact volumes are necessary to provide better comparability. This may improve the development of the MRI suitability of implants and better pulse sequences to finally improve patient care
Published: 5/17/2018
Enthält auch Textversion
Gesehen am 20.01.2020
Wissenschaftlicher Film. Deutschland. 2018
Keywords: Film